Recovery and desistance: what the emerging recovery movement in the alcohol and drug area can learn from models of desistance from offending. (2nd January 2017) - Best, David; Irving, Jamie; Albertson, Kathy
Abstract: In the last 20 years, the recovery movement in alcohol and other drugs has emerged as a major influence on alcohol and drug policy and practice in the UK, US and Australia. In roughly the same period of time, the desistance movement has become increasingly prominent in academic criminology, and is increasingly influential in criminal justice practice, particularly in the area of probation. Furthermore, the populations involved in recovery and desistance research have significant overlap, yet there has been little shared learning across these areas. The current article explores the evolution of thinking around desistance and what lessons it might offer conceptual models of recovery. It will be argued that one of the most important shared assumptions relates to identity change, and the extent to which these identity changes are intrinsically social or 'relational'. The paper will advance a social identity model as a mechanism for understanding the journey to recovery or desistance and the centrality of reintegration into communities for a coherent model and public policy around addiction recovery.